PERFORMANCE ANALYSIS OF ELECTRIC VEHICLE POWERTRAIN SYSTEM WITH MULTY SPEED TRANSMISSION - F. Zainuri (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The rapid development of science and technology affects thedevelopment of all products including motorized vehicles. Thepowertrain system in a vehicle is one of the most important things in itbecause it brings power from the motor to the final drive to producetraction performance. The performance of resulted traction willchange depending on the amount of charge received by the vehicle.The right selection of motor and tranmsission gear ratio is also themain key of vehicle’s proper traction performance. The results of theanalysis of the powertrain electric vehicle (EV) system performancewith two-speed transmission obtained by selecting a transmission ratiothat is suitable for use in a vehicle is a transmission ratio of 1.96 forthe 1st gear and of 1.25 for multy speed, since the traction required bythe motor is not too big to be able to do gearshift and thus the gearshift becomes smoother. Based on the results of friction analysis withtraction, it can be concluded that the vehicle is unable to yield tractionof 6.000 rpm at multy speeds with a 10° road slope, due to the slopedrag higher than the vehicle traction. As a result, the vehicle is onlycapable of traveling at 65.30 km/h at multy speeds and of traveling at49.98 km/h in the 1st gear. Based on the results of friction analysiswith traction, it can be concluded that the vehicle is unable to yieldtraction of 5.000 rpm in gear 1 with a slope of 20°, due to the slopedrag higher than the vehicle thrust/traction. Therefore, the vehicle isonly capable of traveling at 41.65 km/h in the 1st gear and of travelingat 49.98 km/h in the 1st gear.